Mint3 depletion-mediated glycolytic and oxidative alterations promote pyroptosis and prevent the spread of Listeria monocytogenes infection in macrophages - Uematsu, Takayuki (Cell Death Dis, 2021)
Listeria monocytogenes (LM) infection induces pyroptosis, a form of regulated necrosis, in host macrophages via inflammasome activation. Here, we examined the role of Mint3 in macrophages, which promotes glycolysis via hypoxia-inducible factor-1 activation, during the initiation of pyroptosis following LM infection. Our results showed that Mint3-deficient mice were more resistant to lethal listeriosis than wild-type (WT) mice. Additionally, the mutant mice showed higher levels of IL-1β/IL-18 in the peritoneal fluid during LM infection than WT mice. Moreover, ablation of Mint3 markedly increased the activation of caspase-1, maturation of gasdermin D, and pyroptosis in macrophages infected with LM in vitro, suggesting that Mint3 depletion promotes pyroptosis. Further analyses revealed that Mint3 depletion upregulates inflammasome assembly preceding pyroptosis via glycolysis reduction and reactive oxygen species production. Pharmacological inhibition of glycolysis conferred resistance to listeriosis in a Mint3-dependent manner. Moreover, Mint3-deficient mice treated with the caspase-1 inhibitor VX-765 were as susceptible to LM infection as WT mice. Taken together, these results suggest that Mint3 depletion promotes pyroptosis in host macrophages, thereby preventing the spread of LM infection. Mint3 may serve as a target for treating severe listeriosis by inducing pyroptosis in LM-infected macrophages.